Tinjauan Kritis Terhadap Pemikiran Mahathir tentang Kelemahan Budaya Melayu dalam Pembangunan - Asriati, Afifah (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
Malay cultural values ​​that inhibit the development of Malaysia visits by experts in different forms and intensity, even controversial ideas with Mahathir. But Mahathir still saw a radical, rational and consistent with the determination to address them in an executable form of development action alone, although many do not agree. This study tried to find a thought based on three major work of Mahathir in three decades of his thoughts, and also represents good thoughts in the past before becoming prime minister and when he was prime minister of Malaysia for 22 years (1981-2003). Through thought and action, Mahathir is identitification figures and symbols of the resurrection of the Malays and given the title of 'Bapa Pemodenan Malaysia'. The approach used in this study is a qualitative approach with content analysis. Data were collected with the documentation and interview techniques. In general, the results of this study found that Mahathir thoughts about the value of Malay were seen by many as do not support the progress of the Malays.Kata Kunci: Pemikiran Mahathir, Budaya Melayu, Pembangunan